ISIM-ISIM YANG DIJARKAN DAN SEBAB-SEBABNYA - Ali Asrun Lubis (Jurnal Bahasa Lingua Scientia, 2013)
Learning foreign language for people who don,t use it in daily, force them to know much term in Arabic example I’rab term. I’rob is the line each word. One of I’rab symbol in Arabic is Majrur. There are three reason why a word become “jar”, the first starting one of jar letter, the second is Idhofah and Tawabi’, the third followed the letter of majrur.